Economics of government export promotion - Pointon , T (Cranfield University, 1977)
Economics of Government Export Promotion The main thrust of this thesis is concerned with finding a new quantitative method for establishing the value or utility of government export promotion. It is set against a general examination of the role and economics of such activities. This is the first academic study in an area which is of increasing interest to governments of both developed and developing economies because there is no satisfactory quantitative measure. To date, such investment has therefore been in the nature of a blind and open-ended commitment. Specific literature On the subject is sparse. Examination of a wideranging literature was therefore necessary. This included: the "conceptual and historical framework; previous qualitative research; societal or public expenditure accounting; international trade and international trade theory; exporters' marketing needs; and, the major disciplines found in government export promotion. The result was the identification of four avenues of evaluation and.also criteria for the possible development of a new measuring technique. Field research was directed to three main areas: (i) the export promotion organisations of eleven overseas governments; (ii) in-depth research into the United Kingdom's export promotion machine; and, (iii) UK exporting firms using the official export services This revealed the evaluation methods employed by government export promotion organisations in some of the major industrialised economies. Further, it enabled a new methodology to be evolved and pilot-tested. A newlevaluative technique is proposed. Relative to other existing techniques, it should permit a quick,.inexpensive and substantially more realistic estimate of the utility of government export promotion services to be made. The approach is based on exporters' turnover and cost-savings effects.